Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1093/jncics/pkab019
|View full text |Cite
|
Sign up to set email alerts
|

Diet Quality and Breast Cancer Recurrence and Survival: The Pathways Study

Abstract: Background Prior research suggests a relationship between overall diet quality and breast cancer survival, though few studies have reported on this topic. We evaluated whether four dietary quality indices consistent with healthy eating recommendations around the time of breast cancer diagnosis were associated with risk of recurrence, cause-specific and all-cause mortality. Methods A total of 3,660 women diagnosed with invasiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(53 citation statements)
references
References 34 publications
0
45
0
Order By: Relevance
“…The characteristics of included studies are summarized in Table 2. Most of the studies were conducted using prospective (n = 8) [15,[26][27][28]31,[35][36][37] or retrospective (n = 3) [32][33][34] cohort study designs with a mean/median follow-up period of 6-17.2 years, allowing a sufficient time for outcomes to occur, and most studies had excellent follow-up rates upwards of 95%. Nine studies were conducted in the United States, one [34] from Italy, and one [35] from China.…”
Section: Results Of the Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of included studies are summarized in Table 2. Most of the studies were conducted using prospective (n = 8) [15,[26][27][28]31,[35][36][37] or retrospective (n = 3) [32][33][34] cohort study designs with a mean/median follow-up period of 6-17.2 years, allowing a sufficient time for outcomes to occur, and most studies had excellent follow-up rates upwards of 95%. Nine studies were conducted in the United States, one [34] from Italy, and one [35] from China.…”
Section: Results Of the Searchmentioning
confidence: 99%
“…Recently, seven more studies [15,[32][33][34][35][36][37] examined the associations between diet quality and breast cancer-specific outcomes, allowing re-evaluation of such associations with increased statistical power. Therefore, this current meta-analysis aims (1) to examine the associations between diet quality indices/scores and cancer outcomes (i.e., recurrence and mortality) using two approaches: (i) a dietary index as the unit of analysis (index-based analysis) and (ii) a cohort as the unit of analysis (cohort-based analysis) and (2) to examine whether such associations vary according to cancer subtype or participant characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Even fewer studies have examined dietary patterns and breast cancer recurrence, and none emphasized the distinction between healthful and unhealthful plant foods or found associations with recurrence [21]. Several cohorts have examined other popular a priori dietary pattern indices that are not necessarily "plant based" but do emphasize healthful plant foods such as fruits, legumes, and whole grains, e.g., healthy eating index (HEI), dietary approaches to stop hypertension (DASH), and alternative eating index (AHEI) [21][22][23][24]. Consistent with our findings, a majority of these studies have found protective associations of dietary patterns emphasizing healthful plant foods with all-cause mortality and non-breast-cancer mortality [23,25].…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity recommendations should include regular physical activity including 150 minutes of moderate or 75 minutes of vigorous activity with at least 2 days per week of strength training. 3,14,21 Long-Term Side Effects From Breast Cancer and Treatment Advances in the field of oncology have increased survival with increased choices within each modality of treatment, namely surgery, radiation therapy, traditional chemotherapy, hormone therapy, and immunotherapy. Treatment choices are based on tumor characteristics such as tumor size and pathology, and patient comorbidities.…”
Section: Health Promotionmentioning
confidence: 99%
“…Limit the consumption of processed meat and red meat 3. Limit alcoholic beverages to no more than 1 drink daily Exercise recommendations per week to reduce recurrence21 1. Moderate-intensity exercise (walking or bicycling): recommend at least 2.5 hours (150 minutes) to 5 hours (300 hours) per week 2.…”
mentioning
confidence: 99%